Characterization of Caenorhabditis elegans transient receptor potential vanilloid (TRPV) channels and their interactions with insecticidal compounds - Samantha Griffin; Amanda Garbers; Lauren Banina; Trent Perry; Gerald Watson (Pesticide Biochemistry and Physiology, 2025)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Targeting mitochondrial function to inhibit glycolysis and oxidative phosphorylation (OXPHOS) for therapeutic intervention in triple-negative breast cancer line (MDA-MB 231) utilising Cape fynbos - Francis Adu-Amankwaah; Kudzanai Ian Tapfuma; Kudakwashe Nyambo; Gerald Maarman; Brian S.M. Munansangu; Funanani Thagulisi; Daniel J. Watson; Lubbe Wiesner; Ndivhuwo Tshililo; Lawrence Mabasa; Vuyo Mavumengwana; Lucinda Baatjies (South African Journal of Botany, 2025)

Managing wilding pines in the Cape Floristic Region, South Africa: Progress and prospects - Grant Martin; Kim Canavan; Gerald Chikowore; Richard Bugan; Willem De Lange; Ben du Toit; Graham Harding; Ronald Heath; Martin Hill; Brett P. Hurley; Philip Ivey; Debbie Muir; et al. (South African Journal of Botany, 2025)

Padded Helmet Shell Covers in American Football: A Comprehensive Laboratory Evaluation with Preliminary On-Field Findings - Nicholas J. Cecchi; Ashlyn A. Callan; Landon P. Watson; Yuzhe Liu; Xianghao Zhan; Ramanand V. Vegesna; Collin Pang; Enora Le Flao; Gerald A. Grant; Michael M. Zeineh; David B. Camarillo (Annals of Biomedical Engineering, 2024)

Correction: Identifying Factors Associated with Head Impact Kinematics and Brain Strain in High School American Football via Instrumented Mouthguards - Nicholas J. Cecchi; August G. Domel; Yuzhe Liu; Eli Rice; Rong Lu; Xianghao Zhan; Zhou Zhou; Samuel J. Raymond; Sohrab Sami; Heer Singh; India Rangel; Landon P. Watson; et al. (Annals of Biomedical Engineering, 2023)

Plant Functional Types Differ in Their Long-term Nutrient Response to eCO2 in an Extensive Grassland - Ruben Seibert; Louise C. Andresen; Klaus A. Jarosch; Gerald Moser; Claudia I. Kammann; Naiming Yuan; Jürg Luterbacher; Ronnie J. Laughlin; Catherine J. Watson; Martin Erbs; Christoph Müller (Ecosystems, 2022)
Increasing atmospheric CO 2 enhances plant biomass production and may thereby change nutrient concentrations in plant tissues. The objective of this study was to identify the effect of elevated atmospheric CO 2 concentrations on nutrient concentrations of grassland biomass that have been grown for 16 years (1998–2013). The grassland biomass grown at the extensively managed Giessen FACE experiment, fumigated with ambient and elevated CO 2 (aCO 2 ; eCO 2 ; +20%) was harvested twice annually. Concentrations of C, N, P, K, Ca, Mg, Mn, Fe, Cu and Zn were determined separately for grasses, forbs and legumes. Under eCO 2 , the concentration of N was reduced in grasses, Ca was reduced in grasses and forbs, P was reduced in grasses but increased in legumes, Mg concentration was reduced in grasses, forbs and legumes and K was reduced in grasses but increased in forbs. The nutrient yield (in g nutrient yield of an element per m −2 ) of most elements indicated negative yield responses at a zero biomass response to eCO 2 for grasses. K and Zn nutrient yields responded positively to eCO 2 in forbs and Mn and Fe responded positively in forbs and legumes. The results suggest that under eCO 2 the nutrient concentrations were not diluted by the CO 2 fertilization effect. Rather, altered plant nutrient acquisitions via changed physiological mechanisms prevail for increased C assimilation under eCO 2 . Furthermore, other factors such as water or nutrient availability affected plant nutrient concentrations under eCO 2 .

Identifying Factors Associated with Head Impact Kinematics and Brain Strain in High School American Football via Instrumented Mouthguards - Nicholas J. Cecchi; August G. Domel; Yuzhe Liu; Eli Rice; Rong Lu; Xianghao Zhan; Zhou Zhou; Samuel J. Raymond; Sohrab Sami; Heer Singh; India Rangel; Landon P. Watson; et al. (Annals of Biomedical Engineering, 2021)

The impact of oral rehabilitation coupled with healthy dietary advice on the nutritional status of adults: A systematic review and meta-analysis - Laura McGowan; Leigh-Ann McCrum; Sinead Watson; Christopher Cardwell; Bernadette McGuinness; Helen Rutherford; Victoria Paice; Ciaran Moore; Paul R. Brocklehurst; Jayne V. Woodside; Gerald McKenna (Critical Reviews in Food Science and Nutrition, 2020)

A Pore-Scale Investigation of Low-Salinity Waterflooding in Porous Media: Uniformly Wetted Systems - Michael G. Watson; Igor Bondino; Gerald Hamon; Steven R. McDougall (Transport in Porous Media, 2017)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)